Suicide in Kerala, India A Critical Analysis (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
In India, the state of Kerala is considered as Gods own country. This Southern most state of India was cited by Amartya Sen as the model of Development, which shines in various aspects like literacy, secularism, technological pursuits, life expectancy and political upsurge.  At the same time it bears impediments with respect to unemployment among educated youth, alcoholism, divorce and family breakdown. Despite these, another factor that can be added to the dread list is the spiralling suicide rate. The latest figures from the National Crime Records Bureau show that 8,431 people killed themselves during 2010; the State accounted for 6.2 per cent of the total number of suicides in the country. The NCRB data also showed that the national average suicide rate was 11.2 per lakh population during 2010, which was marginally lower than 11.4 per lakh population during 2009 (NCRB Report 2010). Though Keralas per centage share has come down, there has been an increase in the rate of suicide from 24.6 per lakh population in 2009 to 25.3 per lakh population in 2010 which is two times higher than national average; which means one suicide per hour. In fact, 2010 has had the dubious distinction of having witnessed the highest number of suicides in the last five years (NCRB reports 2010). Police sources add that 36 cases of suicide have already registered in the first two months of the current year. For each completed suicide there are 20 times more suicidal attempts. Each suicide, on an average leaves 20 times more people in severe distress (NCRB 2011). Maithri, an NGO in Kerala says that around 100 people attempt suicide every day in Kerala, of whom 25 are successful. More men kill themselves than women, the ratio being 7:3 and 80 per cent of the suicides are by those in the 15 to 59 age group.